Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Berpikir Kritis Siswa Kelas X Di SMA Negeri 11 Kota Jambi - Aldilah, Tia Rosa; Sari, Pratiwi Indah (SJEE (Scientific Journals of Economic Education), 2024)
This research aims to determine the effect of using the Problem Based Learning learning model on the critical thinking abilities of class X students at SMA Negeri 11 Jambi City. This type of research uses quantitative research methods with a descriptive analysis approach and simple linear regression analysis techniques. The results of the research show that the use of the Problem Based Learning learning model has a significant and positive effect on the critical thinking abilities of class X students at SMA Negeri 11 Jambi City. Thus, Problem Based Learning carried out in class X at SMA Negeri 11 Jambi City can improve students' critical thinking.